2017
DOI: 10.4103/0253-7176.211754
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Danger Ideation Reduction Therapy in Obsessive-Compulsive Disorder Washer with Poor Insight: A Case Study and Literature Review

Abstract: Obsessive-compulsive disorder (OCD) is characterized by obsessions and compulsions. Treatment usually consists of serotonergic medications along with exposure therapies. Danger ideation reduction therapy (DIRT) is an alternative therapy predominantly for washing compulsions and focuses on reduction of danger ideations. DIRT was tried on Ms. S. with a history of OCD for 15 years and improvement was noticed on Yale–Brown Obsessive Compulsive Scale, Padua Inventory, Hamilton Anxiety Rating Scale and Hamilton Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[71] A case study reported from India with untreated OC washing behavior showed improvements with symptoms of OCD, insight, and functioning, following 15 DIRT sessions over 2 months. [72] Similarly, a treatment-refractory adolescent (medications as well as ERP) with contamination fears, washing compulsions, and significant avoidance responded to 16 sessions of DIRT. There was substantial improvement in OCD symptoms, depression, and anxiety; these improvements were maintained at 12 months of follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…[71] A case study reported from India with untreated OC washing behavior showed improvements with symptoms of OCD, insight, and functioning, following 15 DIRT sessions over 2 months. [72] Similarly, a treatment-refractory adolescent (medications as well as ERP) with contamination fears, washing compulsions, and significant avoidance responded to 16 sessions of DIRT. There was substantial improvement in OCD symptoms, depression, and anxiety; these improvements were maintained at 12 months of follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…Rational emotive therapy, on the other hand, has been shown to have some possible beneficial effects in OCD (Emmelkamp et al, 1988). Australian researchers have developed danger ideation reduction therapy (DIRT), using rational emotive therapy but with instructions not to undergo exposure for patients with contamination fears; good outcomes in case reports and some small controlled trials have been found (Jones and Menzies, 1998;Krochmalik et al, 2001;Maqbool et al, 2017). The techniques used in DIRT include cognitive restructuring using rational emotive therapy (Ellis, 1962); filmed interviews with people who work in feared situations; corrective information about the real risks of 'contamination' as opposed to the deleterious effects of overzealous hand-washing and attentional focussing whereby patients are taught to focus the mind away from the danger-related intrusive thoughts.…”
Section: Novel Forms Of Psychotherapymentioning
confidence: 99%